2021
DOI: 10.1002/cmdc.202100028
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Sensitised LaF3:Eu3+ and SrF2:Eu3+ Nanoparticles and in Vitro Haemocompatiblity Studies

Abstract: Luminescent Ln 3 + -doped nanoparticles (NPs) functionalised with the desired organic ligand molecules for haemocompatibility studies were obtained in a one-pot synthesis. Chelated aromatic organic ligands such as isophthalic acid, terephthalic acid, ibuprofen, aspirin, 1,2,4,5-benzenetetracarboxylic acid, 2,6pyridine dicarboxylic acid and adenosine were applied for surface functionalisation. The modification of the nanoparticles is based on the donor-acceptor character of the ligand-nanoparticle system, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…In Eu NPs, investigators have seen a range of emission lifetimes in various media (i.e., solid state or in aqueous solutions). Irfanullah and co-workers synthesized sensitizer-capped Eu-doped LaF 3 nanocrystals with an average Eu emission lifetime of 0.41 ms . We observed shorter lifetimes in this work, likely because our measurements were in water, while the reported values for the LaF 3 nanocrystals were measured in the solid state.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In Eu NPs, investigators have seen a range of emission lifetimes in various media (i.e., solid state or in aqueous solutions). Irfanullah and co-workers synthesized sensitizer-capped Eu-doped LaF 3 nanocrystals with an average Eu emission lifetime of 0.41 ms . We observed shorter lifetimes in this work, likely because our measurements were in water, while the reported values for the LaF 3 nanocrystals were measured in the solid state.…”
Section: Resultsmentioning
confidence: 67%
“…Adusumalli and co-workers obtained a double exponential decay with lifetimes of 2.17 and 6.43 ms for TA-capped Eu-doped nanoparticles. 86 These long lifetimes were measured in aqueous media; interestingly, quenching from the presence of the O–H vibrations was not discussed. Atrazine-capped Eu 2 O 3 particles synthesized by Feng and co-workers exhibited a Eu emission lifetime of ∼100 μs.…”
Section: Resultsmentioning
confidence: 99%
“…26 Thus, dipicolinic acid (DPA) was chosen as an antenna to indirectly excite Tb ions in the NPs, as it has been reported to be a very good Tb photosensitizer in complexes 27,28 and as the capping antenna for the NPs. 8,29 Time-resolved excitation spectra of bare and DPA-capped 20% Tb-doped NPs (Figure S10; emission of Tb at 545 nm) show the appearance of an intense and broad excitation band at 270 nm in the presence of DPA, illustrating the antenna effect. Spectroscopic titrations of the various Tb-doped NPs by the DPA ligand were realized.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…70 Advanced studies aimed to find different sensitizers for Eu 3+ in such type of NPs. 74 Therefore, flow cytometry was used to analyse the possible NPs binding to the red blood cell membrane. They showed that these nanomaterials are non-cytotoxic compounds in vitro and can be further investigated for biomedical in vivo applications.…”
Section: A-uv To Visible Conversionmentioning
confidence: 99%
“…In a recent study, Adusumalli et al tested LaF 3 :Eu 3+ and SrF 2 :Eu 3+ NPs photosensitized by different ligands ( 5 , 6 , 10 and 13 ) for their haemocompatibility. 74 Therefore, flow cytometry was used to analyse the possible NPs binding to the red blood cell membrane. They showed that these nanomaterials are non-cytotoxic compounds in vitro and can be further investigated for biomedical in vivo applications.…”
Section: Ln Ion Doped Nps With Capping Photosensitizersmentioning
confidence: 99%